Comparison Differential Transform Method (DTM) and Mohand Transform for Solving Ordinary Differential Equations - Sham, Mohd Shamezan; Abd Latif, Noor Azliza (Enhanced Knowledge in Sciences and Technology, 2025)
This study compares the differential transform method (DTM) and Mohand transform (MT) for solving ordinary differential equations (ODEs) with constant coefficients. The research evaluates the performance of these methods in terms of accuracy and computational efficienct. Three example of ODEs were solved using both method with MATLAB employed for computation and analysis. Numerical and graphical comparisons assessed the solution accuracy and computational feasibility. Result indicate that MT provides exact solutions, while DTM offers computational simplicity but with increases error in larger domains, MT demonstrates superior accuracy, while DTM remains computationally efficient for specific applications.